Survey of Edible Caterpillars in Gbado-Lite City (North Ubangi, Democratic Republic of the Congo) and Medicinal Value of Their Host Plants - Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy; Rakotondrazafy Jennie Irma Norosoa; Ruphin Djoza Djolu; Colette Masengo Ashande; Felix Mboka Mune; John Koyanza Wangombe-Dawe; Michel Mobale Mongeke; Jean-Jacques Domondo Amogu; Blaise Mbembo-Wa-Mbembo; Moises Monizi Mawunu (Britain International for Academic Research (BIAR) Publisher, 2022)
The purpose of this study was to conduct a survey of edible caterpillars and the ethno-medical value of their host plants in Gbado-Lite using the